Fiscal sustainability in the Caribbean: An econometric analysis - Jeetendra Khadan (Inter-American Development Bank (IDB), 2019)
Many countries in the Caribbean have been grappling with persistent fiscal imbalances and rising debt levels. The average debt to GDP ratio in the Caribbean in 2017 was 76.6 percent, higher than the negative debt-growth threshold of 60 percent of GDP. Also, the average fiscal deficit as a percent of GDP was 2.8 percent, but with significant heterogeneity across countries ranging from 0.5 percent to 11 percent. Using the inter-temporal budget constraint framework and various panel data econometric estimators, this article examines the issue of fiscal sustainability for a group of 10 Caribbean countries over the period 1991-2017. The evidence from panel co-integration models of government revenue and expenditure shows that past fiscal behavior is 'weakly' sustainable. The 'weak sustainability' finding is reinforced by evidence from an extended fiscal reaction function which showed that the primary balance improves by about 0.02 for every 1 percentage point increase in the debt ratio.
Keywords: C32; E62; H62; H63; 330; Carribean; fiscal sustainability; intertemporal budget constraint; panel cointegration